Calitatea vieţii în sănătate. Definiţii şi instrumente de evaluare - Lupu, Iustin (Calitatea Vieții, 2006)
In our review paper we try to define the concept of quality of life from contemporary theoretical perspectives. At the same time, we present the typology of generic and specific psychometric instruments used for the evaluation of quality of life in general and dental medicine. In the category of generic instruments are presented the structure and scoring procedures of instruments like: MOS-SF-36, WHOQOL-100, Duke Health Profile, SCL-90-R, Nottingham Health Profile, Sickness Impact Profile-136, and some specific instruments for cardiovascular diseases like: MACNEW, Seattle Angina Questionnaire; for cancer are presented: Rotterdam Symptom Checklist, EORTC QOL-C30, and l, and for pediatric patients PedsQOL-CM-27, and Kindl questionnaires. For oral health status are briefly presented: Dental Impact Profile, Oral Health Impact Profile, Oral Quality of Life Inventory, Oral Health-Related Quality of Life, Oral Impact on Daily Performance.